2010
DOI: 10.1007/s11999-009-0971-y
|View full text |Cite
|
Sign up to set email alerts
|

The Scandinavian Total Ankle Replacement: Survivorship at 5 and 8 Years Comparable to Other Series

Abstract: Ankle arthroplasty is increasingly used to treat advanced ankle arthritis. Earlier prostheses have given way to second-generation implants, on which we are accumulating medium-term data. The Scandinavian Total Ankle Replacement (STAR) is a three-component uncemented implant in wide use in Europe and the only mobile-bearing prosthesis with conditional approval in the United States. We retrospectively reviewed 45 patients (52 ankles) who had primary total ankle replacements using STAR prostheses, in order to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 17 publications
1
50
1
2
Order By: Relevance
“…Three different fixedbearing implants and one newer mobile-bearing implant are approved for use in the United States. Some evidence suggests greater longevity in STAR mobile-bearing prostheses over standard fixed-bearing designs [16,20,28]. Furthermore, the study used for the reference case has the largest reported series of TAAs (200 patients), with some of the longest followup data published (range, 5-13 years), and greater than 80% survivorship [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different fixedbearing implants and one newer mobile-bearing implant are approved for use in the United States. Some evidence suggests greater longevity in STAR mobile-bearing prostheses over standard fixed-bearing designs [16,20,28]. Furthermore, the study used for the reference case has the largest reported series of TAAs (200 patients), with some of the longest followup data published (range, 5-13 years), and greater than 80% survivorship [28].…”
Section: Methodsmentioning
confidence: 99%
“…The complications included were: postoperative infections, major wound problems, nontraumatic bone fractures, implant problems, or osteolysis [20,25]. Other reports of complication rates between 5% and 25% for TAA [1,13,16] and 0.5% to 10% for ankle fusion [13,20,25] were used to establish ranges for sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Despite high numbers of failures in early generations of total ankle arthroplasty (TAA), a continued and increasing interest in the use of these devices for end-stage arthritis as an alternative to arthrodesis of the ankle exists [1][2][3][4][5]. However, while some studies report encouraging mid-term results, the rate of complications after TAA is high compared to total hip and knee replacement [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nie ule ga wąt pli wo ści fakt, że im wcze śniej zo sta nie wdrożo na re ha bi li ta cja po ope ra cyj na, tym szyb ciej ope ro wany osią gnie sa mo dziel ność lo ko mo cyj ną [3,12]. Zgodnie z do nie sie nia mi licz nych au to rów [16,17], przed zabie giem ko niecz na jest do kła da na oce na ukrwie nia plano wa nej do le cze nia ope ra cyj ne go koń czy ny. Za bu rzenia ukrwie nia, jak wspo mnia no po wy żej, mo gą pro waThis approach also results in decreased pain, thus ensuring the achievement of one of the most important goals of surgical treatment.…”
Section: Discussionunclassified
“…Undoubtedly, the sooner postoperative rehabilitation is started, the faster the patient is able to ambulate unassisted [3,12]. According to numerous authors [16,17], it is necessary to carefully assess the blood supply to the limb before the surgery. As stated before, impaired blood supply may result in disturbed surgical wound healing.…”
Section: Discussionmentioning
confidence: 99%